Dampak Globalisasi Terhadap Nilai-Nilai Budaya Lokal Masyarakat Pedesaan Ambulu Jember (Jurnal Motivasi Pendidikan dan Bahasa, 2024)
In the current era of globalization, many local communities throughout the world, including in rural Ambulu, Jember, are experiencing changes in values ​​and customs due to global influences. The local cultural values ​​of the Ambulu rural community are known to be very rich and diverse, but face challenges as a result of rapid globalization. This research aims to identify and analyze the impact of globalization on local cultural values ​​in the rural community of Ambulu Jember, with a focus on how these values ​​persist or change over time. This research uses a qualitative approach by applying contemporary theory from Michael Foucault to analyze the data. The focus of analysis in this research looks at how the discourse and practices of power in society change along with the introduction of global values ​​and how local communities react to these changes. The research results show that the Ambulu community experiences dualism in maintaining local cultural values. On the one hand, there are efforts by the community to maintain old customs and values, while on the other hand, several aspects of local culture have evolved or even been eroded due to the influence of globalization, such as changes in language, social rituals and kinship systems. The impact of globalization on local cultural values ​​demands more inclusive adaptation strategies and more strategic cultural preservation so that rural communities such as those in Ambulu can maintain their cultural identity while receiving the benefits of globalization.